Explicit solutions to the Sharma-Tasso-Olver equation - Abdou, Mohammed Aly; Ouahid, Oubna; Owyed, Saud; Abdel-Baset, A. M.; İnç, Mustafa; Akinlar, Mehmet Ali; Chu, Yu-Ming (Amer Inst Mathematical Sciences-Aims, 2020)
We present new exact traveling wave solutions of generalized Sharma-Tasso-Olver (STO) with variable coefficients using three different methods, namely the extended F-expansion, the new sub-equations, and generalized Kudryashov expansion. We obtain new solutions with the form of solitons, triangular and rational functions. Computational results indicate that these methods are very useful and easily applicable for solving diverse types of differential equations in nonlinear science.
Keywords: extended F-expansion; new sub-equations; generalized Kudryashov expansion method; Sharma-Tasso-Olver equation